Possible Involvement of Fibrinogen and Proteolysis in Surface Activation - Vroman, L; Adams, Ann Lukosevicius (Thrombosis and Haemostasis, 1967)
Among others, the following events occurring at certain liquid/wettable solid interfaces were studied with the recording ellipsometer :A. removal of fibrinogen films by plasmin, by normal intact plasma, and by Streptokinase plus factor XII deficient plasma ;B. adsorption and desorption of normal plasma, and of factor XII deficient plasma by factor XII or Streptokinase, and the effect of epsilon-aminocaproic acid on these types of desorption ; andC. adsorption of rabbit anti-human fibrinogen serum onto human fibrinogen films and onto films deposited by human plasma and other mixtures. All findings thus far appear compatible with the following interpretation. The wettable surfaces used in this study adsorb fibrinogen out of plasma as well as out of fibrinogen solutions. A few minutes after factor XII is activated, the plasma develops a temporary ability to remove a major part of such a fibrinogen film. The remaining part undergoes further changes without further reduction in thickness.“Activator”, formed by addition of Streptokinase to factor XII deficient plasma, is also able to remove fibrinogen film, whether formed by adsorption out of fibrinogen solutions or out of the factor XII deficient plasma itself. The ‘‘activator” activity is inhibited immediately by epsilon-aminocaproic acid, while the activity created by activated factor XII is not.Relationship of present findings to surface activation of factor XII and to the adhesion of platelets is discussed.